О маневрировании колесного транспортного робота - Ларин, В.Б. (Проблемы управления и информатики, 2012)
Для одноланкового і триланкового транспортного робота розглянуто (у кінематичному наближенні) задачу керування роботом при виконанні ним маневру. Маневр включає як фазу руху робота вперед, так і фазу руху в зворотному напрямі. Наведено співвідношення, яке дозволяє вибрати оптимальне значення кута повороту рульового колеса на початку кожної з фаз руху робота. Результати моделювання показали ефективність запропонованого алгоритму керування. In a kinematic approach for a single-link and three-link wheeled transport robot consideration is given to the problem of control of the robot at its executing a maneuver. The maneuver includes both a phase of the robot movement forward and a phase of movement in the opposite direction. It resulted in the relation which allowed one to choose the optimum value of angle of turn of a steering wheel in the beginning of each of phases of movement of the robot. Results of modeling have shown the efficiency of the offered algorithm of control.